3‐Hydroxyazetidine Carboxylic Acids: Non‐Proteinogenic Amino Acids for Medicinal Chemists. Issue 4 (6th March 2013) - Glawar, Andreas F. G.; Jenkinson, Sarah F.; Thompson, Amber L.; Nakagawa, Shinpei; Kato, Atsushi; Butters, Terry D.; Fleet, George W. J.
Abstract The formation from D‐glucose of both enantiomers of 2, 4‐dideoxy‐2, 4‐iminoribonic acid is the first chemical synthesis of unprotected 3‐hydroxyazetidine carboxylic acids. The long‐term stability of 3‐hydroxyazetidine amides is established at acidic and neutral pH and implies their value as non‐proteinogenic amino acid components of peptides, providing medicinal chemists with a new class of peptide isosteres. The structure of N, 3‐O‐dibenzyl‐2, 4‐dideoxy‐2, 4‐imino‐D‐ribonic acid was established by X‐ray crystallographic analysis. An N‐methylazetidine amide derivative is a specific inhibitor of β‐hexosaminidases at the micromolar level, and is only the second example of potent inhibition of any glycosidase by an amide of a sugar amino acid related to an iminosugar.